Lords of the central marches English aristocracy and frontier society, 1087-1265 - Holden, Brock W. (Oxford historical monographs., 2008)
In the Middle Ages, the March between England and Wales was a contested, militarised frontier zone, a 'land of war'. This text examines how the English aristocracy of this borderland organised themselves and their followers in order to survive against the increasing power of their Welsh opponents.